Impact of H-Index in Academicians Visibility - Mohd Norazmi, Nordin; Santibuana, Abd Rahman; Teh Raihana Nazirah, Roslan; Siti Sarah, Maidin; Mohd Saleh, Abbas; Madzlan, Abet; Mohamad Pirdaus, yusoh (Future Publishing Press, 2024)
Publication metrics are a form of determining the quality of the productivity of publishing scientific articles. When a researcher has published many scientific articles in a certain field, then many people will read it and make it reference material. Therefore, the taking and reference by other parties of a researcher's scientific articles need to be evaluated metrically to determine the level of productivity of the researcher and also their academic impact. Based on that, publication metrics are created for evaluation purposes.This metric shows the evaluation of the publication results of articles that have been made. This method can also show the visibility or appearance of the writer in a certain field. Through this metric, a person can exist consistently in his field scientifically based on his own field of study. In today's academic world, metrics that are often used are H-index and i10 index. Both of these indexes are widely used by scientific article data storage in determining the productivity and visibility of a writer or researcher. Compared to H-Index which is used by various iliah article data keeper, i10 index is exclusively created and used by Google Scholar data keeper only.